Cyanobacterial UV Pigments Evolved to Optimize Photon Dissipation Rather than Photoprotection - Aleksandar Simeonov; Karo Michaelian (Biophysica)
An ancient repertoire of ultraviolet (UV)-absorbing pigments which survive today in the phylogenetically oldest extant photosynthetic organisms, the cyanobacteria, point to a direction in evolutionary adaptation of the pigments and their associated biota; from largely UV-C absorbing pigments in the Archean to pigments covering ever more of the longer wavelength UV and visible regions in the Phanerozoic. Since photoprotection is not dependent on absorption, such a scenario could imply selection of photon dissipation rather than photoprotection over the evolutionary history of life, consistent with the thermodynamic dissipation theory of the origin and evolution of life which suggests that the most important hallmark of biological evolution has been the covering of Earth’s surface with organic pigment molecules and water to absorb and dissipate ever more completely the prevailing surface solar spectrum. In this article we compare a set of photophysical, photochemical, biosynthetic, and other inherent properties of the two dominant classes of cyanobacterial UV-absorbing pigments, the mycosporine-like amino acids (MAAs) and scytonemins. We show that the many anomalies and paradoxes related to these biological pigments, for example, their exudation into the environment, spectral coverage of the entire high-energy part of surface solar spectrum, their little or null photoprotective effect, their origination at UV-C wavelengths and then spreading to cover the prevailing Earth surface solar spectrum, can be better understood once photodissipation, and not photosynthesis or photoprotection, is considered as being the important variable optimized by nature.